Municipal Solid Waste Management in Nigeria: A SWOT Analysis and Potential for Biological-Based Treatment Systems - Bringa, Aminu Musa; Abdullahi, Mubarak (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
The uncontrolled discharge of substantial amounts of Municipal Solid Waste (MSW) has emerged as a major concern due to its profound impact on environmental contamination. The improper handling of municipal solid waste (MSW) is a worldwide problem that affects the environment, social equality, and economic stability. Addressing this issue requires comprehensive evaluations and all-encompassing strategies, particularly in developing countries where the unsustainable management of MSW is prevalent. This review makes an effort to summarize the municipal solid waste management (MSWM) practices in Nigeria. To suggest an administration of conceptual knowledge strategy for addressing the MSWM issues in Nigerian municipalities, the strengths, weaknesses, opportunities, and threats for MSWM in Nigeria were analyzed. The study reviews the existing research, knowledge, and regulations on Nigeria's MSWM. Inadequate awareness of the advantages of waste management, producer involvement in waste management, and ineffective application of government rules are all factors that contribute to ineffective waste management by individuals, households, consumers, and waste management firms. For MSWM in Nigeria, the review suggests a biologically based treatment system as a potential for solid waste management in Nigeria, offering a hopeful solution to the current challenges.